2019
DOI: 10.1111/sode.12424
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and relatedness in early adolescent friendships as predictors of short‐ and long‐term academic success

Abstract: This study examined early adolescent autonomy and relatedness during disagreements with friends as key social competencies likely to predict academic achievement during the transition to high school and academic attainment into early adulthood. A sample of 184 adolescents was followed through age 29 to assess predictions to academic success from observed autonomy and relatedness during a disagreement task with a close friend. Observed autonomy and relatedness at age 13 predicted relative increases in grade poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
14
0
1
Order By: Relevance
“…Nonetheless, the finding that these predictions existed at all suggests that perhaps some of the skills needed to maintain close friendships—loyalty, trustworthiness, collegiality—may also set adolescents up for future success in the workplace. Alternatively, it may be that academic attainment, which has been previously found to be predictable from adolescent–peer interactions, may partly mediate this modest link to work performance (Loeb, Davis, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the finding that these predictions existed at all suggests that perhaps some of the skills needed to maintain close friendships—loyalty, trustworthiness, collegiality—may also set adolescents up for future success in the workplace. Alternatively, it may be that academic attainment, which has been previously found to be predictable from adolescent–peer interactions, may partly mediate this modest link to work performance (Loeb, Davis, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In support of friends’ capacities to evaluate one another there is a long history of peer ratings being sensitive to developmental competencies in ways that surpass adult ratings (Cowen et al, 1973). To date, research has found that adolescent friendship qualities can predict self‐worth, anxiety, and depressive symptoms into late adolescence, and romantic life satisfaction later in adulthood (Allen et al, 2020; Loeb, Davis, et al, 2020; Narr et al, 2019). Friendship qualities have not, however, been examined with regard to the prediction of other long ‐ term functional outcomes, nor have they been examined in terms of whether they add anything over and above predictions from parent–adolescent relationship qualities.…”
mentioning
confidence: 99%
“…Exceptions show evidence for the existence of long-term effects. Pre-adolescents who were accepted by peers reached higher levels of education in early adulthood (Loeb et al, 2020 ). Pre-adolescents who were rejected by peers showed decreases in academic development, lower educational attainment, lower job competence, and more unemployment in (early) adulthood (Gest et al, 2006 ; Véronneau et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidentemente, estos aspectos son importantes para cualquier proceso de socialización juvenil, pero quizás lo sean aún más en el caso de la comunicación digital, frecuentemente caracterizada por una abundancia de "relaciones líquidas", que no necesariamente implican vínculos profundos y/o significativos. Investigaciones recientes muestran la influencia positiva de los vínculos fuertes en la adolescencia y juventud en aspectos como el rendimiento académico (Loeb et al, 2020), adicción a sustancias (Allen et al, 2020a) o amortiguar la marginación social (Allen et al, 2020b). Así, apreciamos, una vez más, los diagnósticos clásicos de Bauman (2003) y trabajos afines (Donzelot et al, 2007) sobre el riesgo de fragilización de los vínculos sociales en la sociedad actual.…”
Section: Conclusiones Y Aprendizajesunclassified